Students’ Descriptive Writing Ability Through Interview Text-Based Learning in Junior High School - Ali Maulana; Amal Mohammad Husein Alrishan; Sereen Mousa Jubran (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to describe the ability of seventh-grade students at MTs Al Jamhuriyah, Cinere, Depok, in writing descriptive essays based on interview texts, focusing on substance and language aspects of descriptive writing performance. Methodology: This study used a descriptive qualitative method involving 30 students of class VII A at MTs Al Jamhuriyah, Cinere, Depok. Data were collected through writing assignments based on interview texts, observation, interviews, and documentation. The instrument used was descriptive writing guidelines covering substance and language aspects. Main Findings: The findings showed that students’ ability in writing descriptive essays based on interview texts was still low. No students reached the excellent category, while 2 students (6%) were in good category, 9 students (30%) in fair category, 16 students (53%) in poor category, and 3 students (3%) in very poor category. Novelty/Originality of this study: This study introduces the use of interview texts as a medium for assessing students’ descriptive writing ability, emphasizing both substance and language components. It provides a more specific evaluation of students’ writing performance and identifies weaknesses in transforming interview content into coherent descriptive essays.